A Massive Intestinal Vaso-occlusive Crisis or “Girdle Syndrome” in a 6-year-old Boy Observed as a First Manifestation of Sickle Cell Disease - Knorr, M.; Bienemann, K.; Walde, G.; Kaufhold, A.; Schündeln, M. M. (Klinische Pädiatrie, 2014)
Sickle cell disease is a chronic hematologic disease with variable but often severe systemic symptoms. In this report, we describe a 6-year-old boy presenting with acute bowel pseudo-obstruction. During this episode, previously undiagnosed sickle cell disease was discovered upon peripheral blood smear analysis. The condition was therefore interpreted as a massive intestinal vaso-occlusive crisis or “girdle syndrome”. Conservative treatment with hydration therapy, analgesia and a manual partial exchange transfusion was initiated. The patient fully recovered within 5 days.Conclusion: Girdle syndrome is a rare but severe adverse event associated with sickle cell disease that must be considered as differential diagnosis in patients with sickle cell disease.
Keywords: sickle cell disease; girdle syndrome; bowel pseudo-obstruction; adverse event